The effect of water status on productive and flowering variables in young ‘Arbequina’ olive trees under limited irrigation water availability in a semiarid region of Chile - Beyá-Marshall, Victor (2018)
The intense drought affecting olive production in Northern Chile underscores the need to research non-traditional irrigation strategies to obtain the best crop performance. Accordingly, this study aimed to obtain preliminary data to guide future research on this topic. Different water replenishment levels on crop evapotranspiration (ETc; 13.5, 27.0, 40.5, and 54%) were established in a young orchard, cv. Arbequina, from the end of fruit drop (EFD) to full bloom in the next season. We evaluated the influence of plant water status (Ψstem) and crop load, considered as function of fruit number divided by trunk cross-sectional area, on reproductive and productive variables using multiple linear regressions. Our results show that crop load and Ψstem measured from EFD to harvest affected yield components. Nevertheless, Ψstem had the strongest influence on fruit size, pulp development, oil accumulation, and yield. Oil content and yield were reduced by 54% and 50% for each MPa, respectively, from Ψstem EFD-H − 1.8 MPa, an effect that intensified as crop load increased. During the period of flower development (September–November), the number of flowers per inflorescence and percentage of perfect flowers were reduced when Ψstem was less than − 2.0 MPa. These preliminary results showed that bud differentiation, inflorescence and flower formation are highly sensitive to water deficit.